2001
DOI: 10.1002/jez.1046
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in habituation of the tail flip response in epigean and troglobitic crayfish

Abstract: We demonstrate that the probability of the crayfish, P. clarkii, to tail flip in response to a touch on the dorsal tail fan is dependent on both the size and the behavioral state of the animal. Alterations in the animal's internal physical state, such as when the animal autotomizes its chelipeds, will cause larger-sized animals to tail flip; if they were not autotomized, then no tail flip response would occur. Altering the external environment by removal of water causes small crayfish, which normally habituate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Vision appears to play an important role in fighting behaviours such as following and lunging (Bruski and Dunham, 1987); however, fighting occurs in the absence of vision (Kellie et al, 2001;Li and Cooper, 2002). Taction appears to be important for striking, pushing and antennae tapping (Bruski and Dunham, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vision appears to play an important role in fighting behaviours such as following and lunging (Bruski and Dunham, 1987); however, fighting occurs in the absence of vision (Kellie et al, 2001;Li and Cooper, 2002). Taction appears to be important for striking, pushing and antennae tapping (Bruski and Dunham, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, however, that the responses to the reflective environment might develop sooner and that they might change over time. Others have demonstrated that certain behaviours change with the length of time during which crayfish are socialized (Issa et al, 1999;Kellie et al, 2001;Gherardi and Daniels, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this species of crayfish, individuals which initially show a submissive behavior rarely switch over to a search or rush mode after an interaction, which suggests that an individual may prefer a particular behavioral state, at least during our observational period. Observations also suggest that the pair member that exhibits the greater exploratory behavior when placed into the novel environment is less likely to tail flip upon initial contact, but this observation has not been fully quantified (Kellie et al, 2001). It would also be of interest to examine social hierarchy behaviors using larger groups of these cave crayfish to index each individual within a group as to the level of assertiveness and submissiveness related to size, weight, and physical activity and exploratory behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we looked for the presence or absence of the social display, which is well established in sighted crayfish studies. Previous observations had indicated a behavioral response to white light in this species (Li et al, 2000;Li and Cooper, 2001;Kellie et al, 2001). This study also examined the effect of white light on the behavioral repertoire and dynamics exhibited between pairs of male blind cave crayfish.…”
mentioning
confidence: 98%
“…Fluoxetine (Prozac) is a 52 commonly used medication for altering mood and the therapeutic (Li et al, 2002). Tail flip and behavioral responses were performed as previously de-155 scribed (Kellie et al, 2001;Sparks et al, 2003;Pagé et al, 2007). Concen-156 trated fluoxetine solution was injected into the animal (Listerman et al, 2000).…”
mentioning
confidence: 99%